Vitales Echo. - Tannert, Christoph; Blume, Eugen (Berlin : Künstlerhaus Bethanien GmbH, 2016)
Bechtold, Matias ; Fobbe, Fabian ; Hirsig, Stefan ; Kabizke, Stefanie ; Kannenberg, Daniel ; Kimura, Kanta ; Koberling, Bernd ; Meiran, Marco ; Saks, Adam ; Stauss, Peter ; Steingrimur, Kristjan ; Streuli, Christine ; Zorzor, Filip
Duits
Engels
Tentoonstelling Vitales Echo, Künstlerhaus Bethanien, Berlin, 17.11.2016 - 11.12.2016.
boek